PENERAPAN MODEL PEMBELAJARAN NOVICK UNTUK MEREMEDIASI MISKONSEPSI SISWA PADA MATERI GETARAN HARMONIS - Rasyid Alqadri; Tomo Djudin; Syaiful B.A (Universitas Tanjungpura, 2020)
AbstractThis study aims to determine the effectiveness of the application of Novick's learning model in remediating student's misconceptions on harmonic vibration material in class X SMA Negeri 2 Pontianak. The form of research used was pre-experimental design with one group pre-test post-test design. The data collection tool in the form of 12 multiple choice questions with 3 alternative answers accompanied by open reasons. The sample of this research is the students of class X MIA 1 which consists of 32 people selected as sample saturated with intact group techniques. The results of the test reliability test of 0.68 (strong category). The decrease in the average of misconceptions per student by 73,2%. By using the McNemar test, there was a conceptual change in students with a significance test obtained by average x2hitungrata-rata (162,86) > x2tabel (3,84) for the value of α = 5%, db=1. The effectiveness of applying the learning model Novick in remediating misconceptions is moderate (ΔS = 0.6739). This research is expected to be used as an alternative remediation activity in overcoming misconceptions experienced by students.Keywords: Misconception, Novick Learning Models, Remediation, Vibration of Harmony